2016
DOI: 10.1371/journal.pone.0146809
|View full text |Cite|
|
Sign up to set email alerts
|

Virulent Diuraphis noxia Aphids Over-Express Calcium Signaling Proteins to Overcome Defenses of Aphid-Resistant Wheat Plants

Abstract: The Russian wheat aphid, Diuraphis noxia, an invasive phytotoxic pest of wheat, Triticum aestivum, and barley, Hordeum vulgare, causes huge economic losses in Africa, South America, and North America. Most acceptable and ecologically beneficial aphid management strategies include selection and breeding of D. noxia-resistant varieties, and numerous D. noxia resistance genes have been identified in T. aestivum and H. vulgare. North American D. noxia biotype 1 is avirulent to T. aestivum varieties possessing Dn4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
2
7
0
Order By: Relevance
“…The transcriptomic responses to plant defensive and abiotic stresses have been investigated in a few aphid species, and comparison of enriched GO terms in these studies with those enriched in A. nerii feeding on different toxicity milkweed hosts revealed similarities and differences. Few GO terms enriched in A. nerii feeding on higher toxicity host plants were similarly enriched in stressed aphids in other studies (Bansal, Mian, & Michel, ; Enders et al., ; Li et al., ; Sinha, Chandran, Timm, Aguirre‐Rojas, & Smith, ; Vellichirammal, Madayiputhiya, & Brisson, ). These include “structural constituent of cuticle” (GO:0042302) and “calcium ion binding” (GO:0005509); “structural constituent of cuticle” was enriched in soya bean aphids ( A. glycines ) exposed to abiotic and biotic stressors (Bansal et al., ; Enders et al., ) and “calcium ion binding” was enriched in wheat aphids ( Diuraphis noxia ) exposed to aphid‐resistant wheat (Sinha et al., ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The transcriptomic responses to plant defensive and abiotic stresses have been investigated in a few aphid species, and comparison of enriched GO terms in these studies with those enriched in A. nerii feeding on different toxicity milkweed hosts revealed similarities and differences. Few GO terms enriched in A. nerii feeding on higher toxicity host plants were similarly enriched in stressed aphids in other studies (Bansal, Mian, & Michel, ; Enders et al., ; Li et al., ; Sinha, Chandran, Timm, Aguirre‐Rojas, & Smith, ; Vellichirammal, Madayiputhiya, & Brisson, ). These include “structural constituent of cuticle” (GO:0042302) and “calcium ion binding” (GO:0005509); “structural constituent of cuticle” was enriched in soya bean aphids ( A. glycines ) exposed to abiotic and biotic stressors (Bansal et al., ; Enders et al., ) and “calcium ion binding” was enriched in wheat aphids ( Diuraphis noxia ) exposed to aphid‐resistant wheat (Sinha et al., ).…”
Section: Resultssupporting
confidence: 65%
“…Few GO terms enriched in A. nerii feeding on higher toxicity host plants were similarly enriched in stressed aphids in other studies (Bansal, Mian, & Michel, ; Enders et al., ; Li et al., ; Sinha, Chandran, Timm, Aguirre‐Rojas, & Smith, ; Vellichirammal, Madayiputhiya, & Brisson, ). These include “structural constituent of cuticle” (GO:0042302) and “calcium ion binding” (GO:0005509); “structural constituent of cuticle” was enriched in soya bean aphids ( A. glycines ) exposed to abiotic and biotic stressors (Bansal et al., ; Enders et al., ) and “calcium ion binding” was enriched in wheat aphids ( Diuraphis noxia ) exposed to aphid‐resistant wheat (Sinha et al., ). No overlapping GO terms were found between the A. nerii differentially expressed genes and differentially expressed genes in pea aphids ( A. pisum ) exposed to abiotic stressors (Vellichirammal et al., ) nor in cotton aphids ( A. gossypii ) exposed to several different plant allelochemicals (Li et al., ).…”
Section: Resultssupporting
confidence: 65%
“…Recently, a third potential mode of lowering the Ca 2+ concentration in sieve elements by salivary proteins became apparent (Sinha et al, 2016). Ca 2+ release from the sieve-element ER stacks (Buchen et al, 1983; Sjolund and Shih, 1983; Furch et al, 2009; Hafke et al, 2009) likely contributes to increased mictoplasmic Ca 2+ levels in response to aphid attack.…”
Section: Functional Aspects Of Salivary Proteinsmentioning
confidence: 99%
“…As a speculation, an interference of salivary proteins with the phosphoinositide metabolism, would lead to a reduced IP 3 production, and thus would suppress the release of Ca 2+ ions into the sieve-element lumen. D. noxia biotype-2 aphids that overexpress proteins inhibiting the key enzyme phospopholipase C, relevant for IP 3 formation, are virulent on aphid-resistant wheat plants (Sinha et al, 2016). However, it should be noted that, in contrast to overwhelming evidence for IP 3 involvement in Ca 2+ release in animal cells, the presence of cytosolic IP 3 in plants has not been convincingly demonstrated as yet (Kudla et al, 2010).…”
Section: Functional Aspects Of Salivary Proteinsmentioning
confidence: 99%
“…The authors suggested that the elevated mucin production might enable BPH to cope with the stress of the defense responses or help BPH to suppress the defenses of the resistant plant (Huang et al, 2017). An upregulation in a mucin-17-like isoform X3 transcript was also observed in Diuraphis noxia fed on an aphid-resistant wheat plant in comparison to non-resistant plants (Sinha et al, 2016). In mice immunized with Anopheles gambiae midgut-bound mucin cDNA, increased mortality was observed among mosquitoes fed immunized mice compared to those fed control mice (Foy et al, 2003).…”
Section: Degs Between Ticks Fed On Tick-susceptible and Resistant Cattlementioning
confidence: 99%